Behaviour of PVC encased reinforced concrete walls under eccentric axial loading. (February 2016) - Havez, Amr Abdel; Wahab, Noran; Al-Mayah, Adil; Soudki, Khaled A.
Abstract: Recently, polyvinyl chloride (PVC) has been used as a stay-in-place (SIP) formwork because of its lower cost compared to other materials, durability, and ease to assemble. The PVC SIP formwork used here consists of interconnected elements; panels and connectors that serve as permanent formwork for the concrete walls. In this paper, the behaviour of the PVC encased reinforced concrete walls tested under eccentric compression loading was investigated. The variables were the type of the specimen (PVC encased or control), the longitudinal reinforcement ratio (0.65% or 1.3%) and the eccentricity of the applied load. The PVC encased wall specimens showed superior performance, more ductile and higher capacity when compared to the control wall specimens. An analytical model was developed to predict the ultimate load capacity of the specimens taking into consideration the effect of the PVC on the load carrying capacity of the walls. The calculated and experimental peak loads were in good agreement. Highlights: Eighteen reinforced concrete walls were tested under eccentric axial load. PVC encased wall specimens showed better behaviour compared to the control specimens. VC enhancement increased at lower reinforcement ratios and higher eccentricities. A model accounting for confinement effect is presented.